2017
DOI: 10.1155/2017/6257958
|View full text |Cite
|
Sign up to set email alerts
|

pVAXhsp65 Vaccination Primes for High IL-10 Production and Decreases Experimental Encephalomyelitis Severity

Abstract: Experimental autoimmune encephalomyelitis (EAE) is a demyelinating pathology of the central nervous system (CNS) used as a model to study multiple sclerosis immunopathology. EAE has also been extensively employed to evaluate potentially therapeutic schemes. Considering the presence of an immune response directed to heat shock proteins (hsps) in autoimmune diseases and the immunoregulatory potential of these molecules, we evaluated the effect of a previous immunization with a genetic vaccine containing the myco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Mononuclear cells infiltrated in the CNS were obtained as previously described ( 38 ). Nineteen days after EAE induction, mice were anesthetized with ketamine/xylazine and perfused with 10 mL saline solution.…”
Section: Methodsmentioning
confidence: 99%
“…Mononuclear cells infiltrated in the CNS were obtained as previously described ( 38 ). Nineteen days after EAE induction, mice were anesthetized with ketamine/xylazine and perfused with 10 mL saline solution.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical features were accompanied by a lower frequency of pro-inflammatory T-cells (IFN-γ-producing and Th17), an increase in anti-inflammatory IL-10-secreting T-cells, lower T-cell infiltration, and a greater microglia shift towards an M2 subtype [127]. Experimental vaccination studies also attempt at upregulating the anti-inflammatory Treg cell populations [130]. A vaccine containing pVAX vector, which contained a Mycobacterium leprae-derived gene that encoded heat-shock protein 65 (hsp65), was produced [130].…”
Section: Vaccines As Treatment For Multiple Sclerosismentioning
confidence: 99%
“…Experimental vaccination studies also attempt at upregulating the anti-inflammatory Treg cell populations [130]. A vaccine containing pVAX vector, which contained a Mycobacterium leprae-derived gene that encoded heat-shock protein 65 (hsp65), was produced [130]. After four doses of the pVAXhsp65 vaccine, the vaccinated EAE mice demonstrated higher levels of IFN-γ and anti-inflammatory IL-10 cytokines [130].…”
Section: Vaccines As Treatment For Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in recent years have suggested that peptidebased vaccinations are promising in treating diseases such as cancer and allergic diseases, and some have shown impressive clinical benefits [22][23][24]. Besides, peptide-based vaccination has also been proposed as a promising immunotherapy for autoimmune diseases such as type 1 diabetes mellitus (T1DM) and multiple sclerosis (MS) [25][26][27]. Some studies also have reported encouraging findings on peptide-based immunotherapeutic vaccinations in rheumatic diseases [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%